Reflexiones sobre la eutanasia: ¿nuestra elección? - Montero Ñavincopa, Luz Marlene (2019)
This article seeks to address the issue of euthanasia from a human point of view with legal effects. Trying to explain what euthanasia do is, known as good death or assisted suicide, it pursues that a sick person without a recovery forecast, in a terminal situation and who suffers a lot, could finish with all his suffering, putting an end to his own life for own relief. Then, in which cases could euthanasia be apply, types, and forms according to the execution, analyzing the benefits and damage, if it is a voluntary and conscious decision, given the especial state of health of the person who decides to put an end to his own life, carrying the analysis to an existential, religious, economic, politic, ethical and natural plane, finally giving a full picture of knowledge and thought to help us adopting a well informed and autonomous posture about our own point of view of euthanasia.